GUILLAIN BARRE SYNDROME, THE LEADING CAUSE OF ACUTE FLACCID PARALYSIS IN HAZARA DIVISION - Rehman, Anis -ur-; Idris, Muhammad; Elahi, Manzoor; Jamshed, Jamshed; Arif, Adeel (Journal of Ayub Medical College Abbottabad, 2007)
Background: Acute flaccid paralysis (AFP) can be caused by a number of conditions. A common preventable cause is poliomyelitis which is still being reported in Pakistan, Guillain Barre Syndrome (GBS), also known as Acute Inflammatory Demyelinating Polyneuropathy, is another common cause of acute flaccid paralysis . It is important to recognize GBS in childhood as parents consider all acute flaccid paralysis to be due to poliomyelitis. The present study was designed to know the frequency of different causes of acute flaccid paralysis in Hazara division. Methods : This is a retrospective analysis of cases of acute flaccid paralysis reported from various districts of Hazara division during the period January 2003 to December 2004. Acute flaccid paralysis was diagnosed clinically through history and clinical examination. The underlying cause of acute flaccid paralysis was investigated by appropriate laboratory tests , such as serum electrolytes, cerebrospinal fluid analysis, electromyogram, nerve conduction study and stool culture for polio virus and other enteroviruses . Diagnosis of Poliomyelitis was confirmed by stool testing for poliovirus. Results: 74 patients presented with AFP during the study period. 36 were male and 38 were female. Guillain Barre syndrome and enteroviral encephalopathy were the two leading causes of acute flaccid paralysis . Majority of the cases were reported from Mansehra district. Children of age groups 12 to 24 months and > 96 months constituted the majority (20% each). Conclusion: Guillian Barre syndrome was the leading cause of acute flaccid paralysis reported from various parts of Hazara division. Key Words : Acute, Flaccid Paralysis , Guillain Barre Syndrome, Poliomyelitis .